Strengthening Indonesian Language Teachers' Pedagogical Competencies in the Transformation of 3D Pop-Up Book Teaching Materials Integrated with Augmented Reality - Zulaeha, Ida; Zuliyanti, Zuliyanti; Utami, Santi Pratiwi Tri; Suratno; Hasanudin, Cahyo; Supriyono, Areni Yulitawati (Journal of Community Empowerment, 2025)
The Indonesian Language teacher pedagogical competence strengthening program in Semarang Regency Junior High Schools integrates teaching material innovation in the form of 3D pop-up books with Augmented Reality (AR) technology. The program began with identifying the needs of teachers and students through surveys and interviews, which then served as the basis for developing 3D pop-up books and AR applications in accordance with the national curriculum. Teachers are actively involved through intensive training to master technical and pedagogical aspects so they are ready to implement them in the classroom. The application of this media enriches learning strategies by providing interactive and contextual experiences. Teachers can guide students in understanding the material through 3D visualization and AR interaction, thereby increasing engagement and learning outcomes. Periodic evaluations show the program's effectiveness in strengthening teachers' competencies in utilizing information technology. Additionally, the program designs advanced training and community forums to enhance collaboration and facilitate the sharing of best practices among educators. With a sustainable approach, this program not only improves the quality of Indonesian language learning but also fosters awareness of the importance of integrating digital technology into education. This innovation has the potential to become a widely adopted model for the education community to address the challenges of the digital age.